Symposium 2: Ubiquitous learning, ubiquitous computing, and lived experience - Bruce, Bertram C. (Proceedings of the International Conference on Networked Learning, 2008)
Ubiquitous learning implies a vision of learning which is connected across all the stages on which we play out our lives. Learning occurs not just in classrooms, but in the home, the workplace, the playground, the library, museum, and nature center, and in our daily interactions with others. Moreover, learning becomes part of doing; we don’t learn in order to live more fully, but rather learn as we live to the fullest. It is understandable to see ubiquitous computing necessary for this kind of ubiquitous learning and sufficient to make it possible. Education would certainly be easier to promote if we could simply identify some new technologies that would make ubiquitous learning occur. But the new technologies are neither necessary nor sufficient for this to happen. This chapter argues that it is our vision for ubiquitous learning that matters most, not simply the technical affordances. We need to define ubiquitous learning in an historically legitimate way, one which recognizes the possibilities afforded by the new technologies without reducing the argument to a technocentric position. In 1946, Gwladys Spencer taught about audiovisual materials using a remarkable list. It included expected items such as "blackboards and bulletin boards," but many unexpected ones as well. She included television (in 1946!), showing that she had foresight about its eventual prominence as a communications medium. She also included tools for investigation, such as microscopes, and "models, objects, specimens." She clearly saw that AV materials were more than simply devices for transmitting information. But more striking still is the inclusion of "pantomimes, playlets, pageants, puppet shows, shadow plays" and "trips, journeys, tours, visits." The presence of these says that she saw all of the elements of her list as opportunities for enriching experiences, rather than simply as media for transmitting information. Aside from the details of which tools she had available, the list shows that Spencer had a broad view of how libraries could support learning and, more important, a vision of what learning could be. Today, we are excited about multimedia in education. But what we often mean is simply that a computer display can show students moving pictures with sound. Interactivity is an important additional component. But our vision of what that multimedia really means for learning needs to go beyond the technical features of the display to consider what students can do and how they can extract meaning from their own experiences. Spencer saw that there were many tools and media that could enhance learning. She drew from traditional as well as emerging technologies to lay out a spectrum of possibilities for teaching and learning. Her list suggests an openness to diverse ways of learning and, moreover, a view of learners as active constructors of meaning. In so doing, she shows that ubiquitous learning depends more upon our pedagogy than on our technology. Our vision of ubiquitous learning must maintain at its core a concept of those fundamental human skills. We feel that ubiquitous computing technologies help us solve problems, create/access knowledge, and build community. We feel that they do it in a way that links work, family and friends, learning, and life. But the very seamlessness of these technologies is seductive. Ellul’s concept of the technological milieu is still a propos: "Every technique makes a fundamental appeal to the unconscious." (1964 p. 403). We need to ensure that employing new technologies enhances rather than diminishes our capacity to develop as whole human beings.